Sosialisasi Hierarki Peraturan Perundang-Undangan untuk Meningkatkan Pemahaman Masyarakat terhadap Sistem Hukum Melalui Program PkM - Ahmad Ramdhani; Adil Nabilahi Akbar; Muhamad Rizki (Pusat Riset dan Inovasi Nasional, 2026)
Public legal awareness is an important element in realizing an orderly, just, and law-based social life, as it enables citizens to understand and properly carry out their rights and obligations. In Mekarjaya Village, Gantar District, Indramayu Regency, a low level of public understanding of the hierarchy of laws and regulations is still evident, which has the potential to cause errors in the application of law within families and communities. This condition indicates the need for systematic, contextual, and easily understood legal socialization. This Community Service Program aims to improve the understanding of members of the Paguyuban Istri Peduli regarding the hierarchy of laws and regulations, while strengthening their role as agents for disseminating legal information within the surrounding community. The method employed is descriptive qualitative with a participatory approach through the delivery of materials, interactive discussions, question-and-answer sessions, and joint reflection. Data were collected through direct observation, oral question-and-answer sessions, and participant feedback forms. The results show an increase in participants’ understanding, high levels of participation in discussions, and the ability to relate legal concepts to real conditions. These findings confirm that participatory-based legal socialization is effective in enhancing public legal awareness and encouraging active community involvement at the local level.